You first set it up as long division.
Second you would find out how many times 6 goes into 67, so count by 6's until you get close 67.
Third once you get that number you write it on top of the long division and then you would subtract whatever that number is below which is 66 because 6 * 11= 66.
So then you would subtract 67 minus 66 which would be 1. Then go from there and you'll get your answer.
Hope this helps!
(5ab-4a-8)-(9ab-5)
Ok just remember that the minus sign before the (9ab-5) is like a minus 1 so it changes the sign inside the bracket...
>>5ab-4a-8-9ab+5
>>-4ab-4a-3
I'm guessing you just have to leave it like that unless there are other parts to the question or whatever but that's that simplified as far as it can be!
Answer:
(3, 1)
Step-by-step explanation:
x+5y=8
-x+2y=-1
-------------
7y=7
y=7/7=1
x+5(1)=8
x+5=8
x=8-5=3
Answer: x=3, y=1.
3.25 is the answer
Step-by-step explanation:
you would add them as decimals